Формування професійної компететності вертольотчиків у закладах вищої освіти авіаційного профілю із специфічними умовами навчання - Марченко, О. Г.; Marchenko, O. H.; Онипченко, П. М.; Onypchenko, P. M.; Марченко, В. В.; Marchenko, V. V.; Ольга Марченко (Науковий вісник Льотної академії. Серія : Педагогічні науки. - 2023. - Вип. 13. - С. 90-100, 2023)
У статті розглянуто особливості формування професійної компетентності курсантів-вертольотчиків у закладах вищої освіти авіаційного профілю із специфічними умовами навчання. Одним із суттєвих критеріїв щодо визначення рівня сформованості особистісної компоненти професійної компетентності вертольотчика є його фахова надійність, яка визначається нормою нальоту, працездатністю, виконавською дисципліною, що у свою чергу є основою та гарантією безпеки польотів.

Under objective conditions (updating the fleet of aviation equipment, equipping it with the latest technologies, a limited training period, the problem of coordinating the terms of flight training and the implementation of training programs of general and professional training cycles, performing a significant amount of practical and professional tasks on simulators and simulators, which only simulate a real flight, etc.) the formation of the entire spectrum of professional competences of helicopter pilots in the process of training in higher education institutions of the aviation profile with specific training conditions is problematic. Taking into account the above, the professional competence of a helicopter pilot will be understood as his flight qualification acquired during the implementation of the professional training system, which traditionally consists of three main blocks: basic education, professional theoretical training, as well as specialization, that is, practical training, which is carried out according to the programs of the primary flight training and training of aviation specialists by appointment. Accordingly, in the structure of the professional competence of a helicopter pilot, it is possible to distinguish a theoretical-knowledge (cognitive) and a practical-activity component. The cognitive component of professional competence involves the constant use of knowledge of technological and methodological bases, searching for data in space that will help in forming a decision to improve the professional level. The operational component integrates the ability to organize flight work, perform flight tasks qualitatively and mobility (justification of the flight task, level of complexity, time and conditions of execution, requirements for the level of preparedness of the crew), control and make corrections in one's activities. It should be noted that the basis of a helicopter pilot's professional reliability is his psychological reliability, which is realized thanks to the determinants of the cadet's volitional sphere, among which the decisive ones are a conscious attitude to flying work, an attitude towards the gradual mastery of flying skills and long-term flying activity. Therefore, the professional competence of a helicopter pilot includes a wide range of theoretical knowledge and practical skills regarding the organization of flight work, high-quality performance of flight tasks in dynamic conditions of specific natural and artificial environments.

В статье рассмотрены особенности формирования профессиональной компетентности курсантов-вертолетовчиков в учреждениях высшего образования авиационного профиля со специфическими условиям обучения. Одним из существенных критериев по определению уровня сформированности личностной компоненты профессиональной компетентности вертолетчика является его профессиональная надежность, определяемая нормой налета, работоспособностью, исполнительской дисциплиной, что, в свою очередь, является основой и гарантией безопасности полетов.
Formation of professional competence of helicopter pilot in institutions of higher education aviation profile with specific learning conditions
Keywords: заклади вищої освіти авіаційного профілю із специфічними умовами навчання; institutions of higher education of the aviation profile with specific study conditions; заведения высшего образования авиационного профиля со специфическими условиями обучения; професійна компетентність; professional competence; профессиональная компетентность; вертольотчик; helicopter pilot; вертолетчик; військовий фахівець; military specialist; военный специалист; професійна підготовка; professional training; профессиональная подготовка